2008
DOI: 10.1620/tjem.214.247
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Sulphonylurea Receptor Subunits, SUR2A and SUR2B, in Rat Renal Tubular Epithelium

Abstract: ATP-sensitive K + (K ATP ) channels in the kidney are considered to play roles in regulating membrane potential according to changes in the intracellular ATP concentration. They are composed of two types of subunits; the pore subunits (Kir6.1, Kir6.2), which are members of the inwardly rectifying K + channel family, and the regulatory subunits, the sulphonylurea receptors, which belong to the ATP-binding cassette (ABC) superfamily. The sulphonylurea receptors (SURs) are receptors of sulphonylureas widely used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…While nicorandil has a dual function in which it is able to donate NO and stimulate the ATP-dependent K channel, the protective effect on podocytes is likely through opening of ATP-dependent K channels (37) because a cGMP signal, as a second messenger of NO, was not detected in the glomerulus. With respect to the localization of SUR-2 in the kidney, Zhou et al (38) found that SUR-2 is expressed in tubular epithelial cells, yet their finding is distinct from our results. However, such discrepancy could be explained by the difference in species or antibody used.…”
Section: Discussioncontrasting
confidence: 99%
“…While nicorandil has a dual function in which it is able to donate NO and stimulate the ATP-dependent K channel, the protective effect on podocytes is likely through opening of ATP-dependent K channels (37) because a cGMP signal, as a second messenger of NO, was not detected in the glomerulus. With respect to the localization of SUR-2 in the kidney, Zhou et al (38) found that SUR-2 is expressed in tubular epithelial cells, yet their finding is distinct from our results. However, such discrepancy could be explained by the difference in species or antibody used.…”
Section: Discussioncontrasting
confidence: 99%
“…The tissue distributions of SUR2A and SUR2B are also distinct. SUR2A is expressed at high levels in cardiac ventricle [but not in the rodent atrium (18)], skeletal muscle, and ovary and at moderate levels in brain neurons, tongue, and pancreatic islets (18,371,932); SUR2B is more widely expressed, for example, in vascular smooth muscle, heart, cardiac specialized conduction system myocytes, vascular endothelium, lung epithelium, hair follicles, renal proximal tubules, renal tubular epithelial cells, microglia, astrocytes, and the dentate gyrus (48,50,86,144,439,491,496,626,637,705,734,906,907,932,933). The transcriptional mechanisms responsible for the differential tissue distributions of SUR2A and SUR2B remain to be elucidated.…”
Section: Regulatory Subunits: the Sulfonylurea Receptorsmentioning
confidence: 99%
“…SURs are present in a wide variety of extra-pancreatic tissues (Gribble & Reimann, 2003). Investigations indicated that SUR2, one common subtype of SUR, is located in PTECs (Zhou et al 2008; Szamosfalvi et al 2002). Hence, it is conceivable that SUs could act directly on the PTECs.…”
Section: Introductionmentioning
confidence: 99%